The Caricom Single Market & Economy (CSME) : freedom of movement; or lack thereof? - Wickham, Peter W. (2003)
Demonstrates that little substantive progress has been made on the issue of freedom of movement. Notes that the right to live and work throughout the region has been diaggregated from 'hassle free travel' which has emerged as a less ambitious short term objective. Suggests that CARICOM has avoided creating the 'right' to live and work throughout the region, while promoting a right to 'seek work' among select Caribbean nationals.